Analisis Yuridis Fungsi dan Peran Jamsostek Dalam Perlindungan Hukum Tenaga Kerja - Achmad Fitrian (Jurnal Penelitian Hukum Legalitas, 2015)
Social Security Labor was held in response to the principle of protection of labor rights include the right to earn a decent living, the right to receive annuity, the right to guaranteed employment injury, and others. The rights of labor above are a matter that requires a guarantee. This study is a normative legal research by using a normative juridical approach. Thus, the object of research is the rule of law embodied in the rules of law created and established by the government; in the amount of statutory legislation and policies directly related to social security. The results of this study were the function and role of the Program Jamsostek to labor protection is not yet maximal conducted by the company of Jamsostek (Persero), this is due to the synergy between labor inspectors and the association of employers and law enforcement officials have not make sense as a whole that the program Jamsostek is a state program that shall be carried out jointl